Biodegradation of chlorinated organic pesticides endosulfan and chlorpyrifos in soil extract broth using fungi. Issue 3 (20th June 2019) - Bisht, Jyoti; Harsh, N.S.K.; Palni, Lok Man S.; Agnihotri, Vasudha; Kumar, Anuj
Abstract: The present study was designed to screen 20 fungi for their potential to degrade the chlorinated organic pesticides endosulfan and chlorpyrifos. Fungi were first screened for their tolerance to various concentrations of target pesticides using soil extract agar and subsequent degradation studies were performed in soil extract broth containing 25 mg/L of the individual pesticide. Pesticide degradation was evaluated using gas chromatography. Other parameters, such as pH and mycelial weight, were also determined. Based on percent growth inhibition of test fungi and subsequent analysis of EC50 values, the overall results revealed that chlorpyrifos showed significantly more growth inhibition in all tested fungi compared with endosulfan. Trametes hirsuta showed complete degradation of both α‐ and β‐endosulfan isomers and Cladosporium cladosporioides displayed maximum degradation of chlorpyrifos. All test fungi degraded endosulfan more efficiently than chlorpyrifos, except Phanerochaete chrysosporium, Trichoderma harzianum, and Trichoderma virens which showed higher degradation of chlorpyrifos than endosulfan. It was also found that all tested fungi degraded α‐endosulfan more efficiently than β‐endosulfan. Endosulfan sulfate was found to be the major degradation product with all tested fungi. Fungi which showed more endosulfan degradation also produced more endosulfan sulfate. However, less endosulfan sulfate was detected with T. hirsuta and Trametes versicolor, although they degraded endosulfan more efficiently.